Prognosis prediction of motor outcome in hemiparetic patients with anterior choroidal artery infarction: Radiologic and transcranial magnetic stimulation prognostic validation studies (STROBE). Issue 51 (23rd December 2021) - Jang, Sung Ho; Lee, Jun; Kim, Jae Woon; Choi, Kyu Tae
Abstract : Abstract: To investigate prognosis prediction of motor outcome in anterior choroidal artery (AChA) infarction patients using radiologic and transcranial magnetic stimulation (TMS) studies. Twenty six patients with complete weakness of the affected hand were recruited. The Motricity Index (MI), Medical Research Council (MRC) scores for the affected finger extensors, Modified Brunnstrom classification (MBC) and Functional Ambulation Category (FAC) were evaluated twice: at onset and the chronic stage (3–4 months after onset). Patients were assigned according to the presence of infarction at the corona radiata (CR); the CR-positive group (infarct presence at the CR and posterior limb of internal capsule [PLIC], 11 patients) and CR-negative group (infarct presence at the PLIC, 15 patients), and the presence of motor evoked potentials at the affected hand muscle: the TMS-positive group (11 patients) and the TMS-negative group (15 patients). At the second evaluation, the MI scores were significantly different between the CR-positive (45.10 ± 7.06) and CR-negative groups (57.90 ± 11.56), and between the TMS-positive (60.37 ± 11.53) and TMS-negative groups (46.70 ± 7.99) ( P  < .05). The MRC scores for the finger extensors were also significantly different between the CR-positive (0.95 ± 1.01) and CR-negative (2.57 ± 1.33) groups and between the TMS-positive (3.05 ± 0.88) and TMS-negative (1.03 ± 1.14) groups ( P  < .05). Fourteen (53.85%) of the 26 patients recovered to have a functional hand score (MBC ≥5) and 19 (73.07%) of the 26 patients recovered to have an independent gait score (FAC ≥3) on their second evaluation. The results show that CR involvement in addition to the presence of a PLIC lesion and a TMS-negative response were related to poor motor outcomes in patients with an AChA infarction. Consequently, radiologic and TMS studies can be considered for motor outcome prognosis prediction in patients with an AChA infarction.